Anaemia and Nutritional Status of Adolescent girls and Policy interventions in India: A Roadblock for Sustainable Development - Gautam, Upma; Tewari, Deeksha Bajpai; Gautam, Upma; Das, Priya (European Journal of Sustainable Development, 2023)
Thesis Statement: National and international policy documents have consistently placed a premium on adolescent nutrition improvement. While the health and well-being of children aged 14 to 19 is a critical indicator of a country's economic growth, the same is always argued to be even more so for females of the same age. Malnutrition's detrimental effects on young females aged 14–19 is of particular concern to health planners. Methodology: Using data from the NFHS-03 (2005–06), NFHS-04 (2015–16), and NFHS-05 (2019-20) surveys, the current study examines the impact of two key policies, the Rashtriya Kishor Swasthaya Karyakram (2019-20) and the Adolescent Reproductive and Sexual Health Program (2005–2014) on the health status of adolescent girls. Results: The study found a strong link between adolescent nutritional and anaemic status, teen pregnancy, and child marriage. Additionally, the disparity between resources allocated and expenditure under Rashtriya Kishor Swasthaya Karyakram has a detrimental effect on the nutritional status of adolescent girls in Indian states. Conclusion and implications: Given that, despite legal interventions, child marriage and teenage pregnancy continue to occur in Indian states, policy interventions and serious implementation become essential for not only improving the health of the female cohort, but also for the future well-being of the next generation. Literacy levels of women and their anaemic status bear a significant negative correlation. Not just the literacy levels, but longer the time the girls have attended school also has a significant negative impact on their anaemic status. Thus, literacy and health and wellbeing of adolescent Indian women bear a significant relationship and poses to be two sides of a coin. Keywords: Adolescent girls, Adolescent Reproductive and Sexual Health Program, Anaemia, Nutrition, Sustainable development goals